2004
DOI: 10.1521/pedi.18.3.226.35445
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in Borderline Personality Disorder: Prevalence, Risk Factors, Prediction, and Prevention

Abstract: Suicidal behavior is frequent in patients with borderline personality disorder (BPD); at least three-quarters of these patients attempt suicide and approximately 10% eventually complete suicide. Borderline patients at greatest risk for suicidal behavior include those with prior attempts, comorbid major depressive disorder, or a substance use disorder. Comorbidity with major depression serves to increase both the number and seriousness of the suicide attempts. Hopelessness and impulsivity independently increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
259
3
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(294 citation statements)
references
References 54 publications
11
259
3
21
Order By: Relevance
“…People with mental disorders die prematurely for a variety of reasons, including poor physical health [3][4][5], adverse physiological consequences of long term psychotropic medication, unhealthy lifestyle [5], as well as increased death rates as a result of suicide, accidents and homicide [6][7][8]. The risk of increased mortality has been shown to vary according to type of mental disorder, with substance use disorders conferring a particularly high risk of early death [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…People with mental disorders die prematurely for a variety of reasons, including poor physical health [3][4][5], adverse physiological consequences of long term psychotropic medication, unhealthy lifestyle [5], as well as increased death rates as a result of suicide, accidents and homicide [6][7][8]. The risk of increased mortality has been shown to vary according to type of mental disorder, with substance use disorders conferring a particularly high risk of early death [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…13 The association between borderline personality disorder specifically and the risk of suicide has been well documented and this is the case particularly when comorbid with major depressive disorder, which is common in this age group. 2,[14][15][16][17] In older adult patients who do go on to complete suicide successfully, it has been found that the majority (77%) had a known underlying mental health condition, with personality disorders making up a very significant proportion (44%). 18 It is therefore apparent that a failure to identify these diagnoses could be catastrophic.…”
Section: Clinical Presentation Of Personality Disorders In Older Adultsmentioning
confidence: 99%
“…We expected the LPI would be moderately correlated with depression, demonstrating convergent validity; the LPI is intended to measure BPD features, which often present with misery, hopelessness, or full diagnoses of depression [28][29][30]. We also expected LPI scores to correlate moderately with suicidal ideation, as suicidal thoughts are highly prevalent among individuals with BPD features [29].…”
mentioning
confidence: 99%
“…We also expected LPI scores to correlate moderately with suicidal ideation, as suicidal thoughts are highly prevalent among individuals with BPD features [29].…”
mentioning
confidence: 99%